Antisense transcription represses Arabidopsis seed dormancy QTL DOG1 to regulate drought tolerance. (13th October 2017) - Yatusevich, Ruslan; Fedak, Halina; Ciesielski, Arkadiusz; Krzyczmonik, Katarzyna; Kulik, Anna; Dobrowolska, Grazyna; Swiezewski, Szymon
Abstract: Plants have developed multiple strategies to sense the external environment and to adapt growth accordingly. Delay of germination 1 ( DOG1 ) is a major quantitative trait locus (QTL) for seed dormancy strength in Arabidopsis thaliana that is reported to be expressed exclusively in seeds. DOG1 is extensively regulated, with an antisense transcript ( asDOG1 ) suppressing its expression in seeds. Here, we show that asDOG1 shows high levels in mature plants where it suppresses DOG1 expression under standard growth conditions. Suppression is released by shutting down antisense transcription, which is induced by the plant hormone abscisic acid (ABA) and drought. Loss of asDOG1 results in constitutive high‐level DOG1 expression, conferring increased drought tolerance, while inactivation of DOG1 causes enhanced drought sensitivity. The unexpected role of DOG1 in environmental adaptation of mature plants is separate from its function in seed dormancy regulation. The requirement of asDOG1 to respond to ABA and drought demonstrates that antisense transcription is important for sensing and responding to environmental changes in plants. Synopsis: Antisense transcription from the same locus is required for DOG1 silencing in mature Arabidopsis plants under non‐stress conditions. Drought and ABA signalling alleviate asDOG1 expression, promoting DOG1 sense transcription and drought tolerance. Antisense DOG1 transcript ( asDOG1 ) is negatively regulated by drought and ABA. asDOG1 silencing results in DOG1 sense expression in mature Arabidopsis plants. Antisense transcription is crucial for the perception of drought/ABA signals. DOG1 confers drought tolerance. Abstract : Antisense transcription from the same locus is required for DOG1 silencing in mature Arabidopsis plants under non‐stress conditions. Drought and ABA signalling alleviate asDOG1 expression, promoting DOG1 sense transcription and drought tolerance.